FRI0364 Fertility in behçet's syndrome: structured interview in a multidisciplinary center. (23rd January 2014) - Saygin, C.; Uzunaslan, D.; Hatemi, G.; Tascilar, K.; Yazici, H.
Abstract : Background: Behçet's Syndrome (BS) follows an active course during the child-bearing years in both men and women. Whether fertility is decreased among the BS patients due to the condition itself or to the frequently used medications like cyclophosphamide (CYC), azathioprine or colchicine is not clear. Objectives: To determine the infertility rate, and the effect of drugs and types of organ involvement on fertility in BS patients. Methods: We included BS patients with and without major organ involvement, familial Mediterranean fever (FMF), ankylosing spondylitis (AS) patients and healthy controls recruited from hospital staff. In order to show a 20% increase in infertility in BS with 0.05 alpha and 80% power, we calculated that each group should contain at least 125 individuals. Among patients who visited the clinic for routine controls, individuals with an even waiting list number were selected. A structured interview was performed by two physicians and medical records were reviewed. Infertility was defined as the inability to conceive after one year of unprotected intercourse. We compared the differences in the proportion of individuals who had never conceived in their lifetime, who had a successful conception but became infertile after disease onset, and individuals who conceived late or with assisted reproductive technology (ART), between BS and control groups. Finally infertility was separately assessed in a group of 62 patients who had used CYC and was compared to that observed among patients with major organ involvement who were CYC naïve. Multivariate logistic regression analysis was used to determine the association of infertility with involved organs and the drugs which were used. Results: The numbers of subjects who were not able to ever conceive, who were not able to conceive only after disease onset, and who were able to conceive late or only with ART were not increased among patients with BS (Table ). There were more FMF patients who conceived late or only with ART. Average number of children, miscarriages, terminations and ectopic pregnancies were not significantly different in patients with BS. The number of infants with reported congenital anomalies was not increased in BS patients and the most commonly reported anomalies were cardiovascular defects and cleft lip/palate. Univariate logistic regression showed an increased risk of infertility with CYC (OR 6.1, %95 CI 0.7-54.2), however this effect was not confirmed in multivariate analysis. This was attributed to a type II error caused by the low number of patients who had used CYC. Finally the infertility was higher among the separate group of 62 CYC users as compared to the patients with major organ disease who were CYC naive (7/20 vs 3/60 among those who atttempted to conceive, p=0.002) Conclusions: Infertility rate is not appreciably increased among BS patients as compared to FMF patients, AS patients and healthy controls. Major organ involvement does not seem to affect this. CYC is the only drug which seems to decrease fertility in BS. Disclosure of Interest : None Declared